2023
DOI: 10.1177/15248380231207894
|View full text |Cite
|
Sign up to set email alerts
|

The Family Context in Cybervictimization: A Systematic Review and Meta-Analysis

Raquel Lozano-Blasco,
Alejandra Barreiro-Collazo,
Borja Romero-Gonzalez
et al.

Abstract: The use of Information and Communication Technologies is clearly widespread among adolescents from a young age. Although it poses a significant contribution at the academic, social, and emotional levels, it can also involve a set of important risks, including cyberbullying and, therefore, cybervictimization. Previous studies have pointed out the importance of family context since parental control and family communication emerge as contributors to this phenomenon. Therefore, the aim of the present study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 108 publications
1
1
0
Order By: Relevance
“…Our results revealed that only the dimensions of parental rejection were relevant in protecting or putting children at risk of being bullied in the online context and are in line with those previously reported in a systematic review, where parental warmth was shown to be a protective factor (Elsaesser et al, 2017), and with those reported in a recent meta-analysis, where parental aversiveness, in the form of parental offensive communication, was found to be a risk factor (Lozano-Blasco et al, 2023). A parent child-relationship characterized by a warmth and affection may create an environment in which children are more likely to disclose bullying incidents (Liu et al, 2020).…”
Section: The Effects Of Parental Factors On Traditional and Cyberbull...supporting
confidence: 91%
“…Our results revealed that only the dimensions of parental rejection were relevant in protecting or putting children at risk of being bullied in the online context and are in line with those previously reported in a systematic review, where parental warmth was shown to be a protective factor (Elsaesser et al, 2017), and with those reported in a recent meta-analysis, where parental aversiveness, in the form of parental offensive communication, was found to be a risk factor (Lozano-Blasco et al, 2023). A parent child-relationship characterized by a warmth and affection may create an environment in which children are more likely to disclose bullying incidents (Liu et al, 2020).…”
Section: The Effects Of Parental Factors On Traditional and Cyberbull...supporting
confidence: 91%
“…In such an environment, if the family lacks organization and rules are unclear, adolescents may feel a lack of guidance and structure ( 39 ), thus more likely to become immersed in the online world to seek self-organization and rules. Simultaneously, we will also explore the relationship between family environment and adolescent internet addiction in the dimensions of cohesion ( 40 ), conflict resolution ( 41 ), achievement orientation ( 42 ), cultural interest ( 43 ), and recreational activities ( 44 ). Therefore, this paper also aims to investigate the relationship between family environment and adolescent internet addiction across these dimensions, seeking to identify family environmental factors that predict adolescent internet addiction.…”
Section: Introductionmentioning
confidence: 99%